Assessing the Relationship Between Internet Banking and Investment Decision Through Sustainability and Competitive Advantage: Evidence From Congolese Banks - Wu, Mengyun; Pea-Assounga, Jean Baptiste Bernard (Frontiers in Psychology, 2022)
Competitive advantage and sustainability emerge as important factors for the success of an organization's overall differentiation. This research aims to identify the relationship between internet banking and bank investment decision, as well as gaging the mediating effects of sustainability and competitive advantage as attributes of investment decisions. To achieve that, a questionnaire was administrated to banks’ employees and customers. To carry out the hypotheses testing, we have employed the structural equation modeling through SPSS and SmartPLS. The findings suggest that internet banking, sustainability, and competitive advantage constructs are significant antecedents of banks because they highlight valuable attributes for banks to attain future benefits. This paper contributes to banks managers and scholars by providing a framework and supporting theories that help to identify relevant constructs and strategic resources characteristics. From the findings, we recommend conducting future studies in other countries or fields to generalize our results.